Agricultural Policies and Trade Paths in Turkey - Larson, Donald F.; Martin, Will; Sahin, Sebnem; Tsigas, Marino (World Bank Group, Washington, DC, 2014)
In 1959, shortly after the European Economic Community was founded under the 1957 Treaty of Rome, Turkey applied for Associate Membership in the then six-member common market. By 1963, a path for integrating the economies of Turkey and the eventual European Union had been mapped. As with many trade agreements, agriculture posed difficult political hurdles, which were never fully cleared, even as trade barriers to other sectors were eventually removed and a Customs Union formed. This essay traces the influences the Turkey-European Union economic institutions have had on agricultural policies and the agriculture sector. An applied general equilibrium framework is used to provide estimates of what including agriculture under the Customs Union would mean for the sector and the economy. The paper also discusses the implications of fully aligning Turkey's agricultural policies with the European Union's Common Agricultural Policy, as would be required under full membership.